The rise of the platform marketer : - Dempster, Craig (John Wiley and Sons, 2015)
Develop the skills and capabilities quickly becoming essentialin the new marketing paradigm The Rise of the Platform Marketer helps you leverage the"always-on" consumer to deliver more personalized engagementsacross media, channels, and devices. By managing these interactionsat scale throughout the customer lifecycle, you can optimize thevalue of your customers and segments through strategic use ofConnected CRM (cCRM). This book shows you how to take advantage ofthe massive growth and proliferation of social and other digitalmedia, with clear strategy for developing the new capabilities,tools, metrics, and processes essential in the age of platformmarketing. Coverage includes identity management, audiencemanagement, consumer privacy and compliance, media and channeloptimization, measurement and attribution, experience design, andintegrated technology, plus a discussion on how the company as awhole must evolve to keep pace with marketing's increasingly rapidevolution and capabilities.